Trends in modern power systems resilience: State-of-the-art review. (July 2022) - Younesi, Abdollah; Shayeghi, Hossein; Wang, Zongjie; Siano, Pierluigi; Mehrizi-Sani, Ali; Safari, Amin
Abstract: The power system is vital to energy security, emergency services, critical infrastructures, and the economy. Resilience of the power system against high-impact low-probability events is of particular importance to ensure the stability and reliability of the system planning and operation. The challenges and opportunities towards both the evaluation and improvement of resilience of the power system are explicitly reviewed in this paper. Appropriate criteria with a comprehensive understanding of resiliency are emphasized. In addition, to improve the modern power system resilience, this article considers the short and long-term plans with different categorizations, along with a detailed analysis of the corresponding challenges. Short-term plans refer to resilience-oriented scheduling, and long-term plans indicate fundamental corrections such as hardening and equipment upgrades. Practical methods are discussed in the paper to evaluate and improve the modern power system resilience. Furthermore, some common metrics for long-term and short-term resilience assessment are evaluated and compared. The investigations have shown that microgrids have a high potential to improve resilience of the power system by bringing energy sources closer to load centers, and reducing the grid dependence on transmission lines, which are the most vulnerable equipment against natural disasters. Highlights: Reviewing the resources and methods proposed for modern power systems resilience from the perspective of smart grids. Revealing the great potentials of smart grids in improving power system resilience considering a critical point of view. Assessing the proposed mathematical metrics for power grid resilience in terms of inclusion and definition.